Guanylyl cyclase C in colorectal cancer: susceptibility gene and potential therapeutic target. (May 2009) - Lin, Jieru E; Li, Peng; Pitari, Giovanni M; Schulz, Stephanie; Waldman, Scott A
Colorectal cancer is one of the leading causes of tumor-related morbidity and mortality worldwide. While mechanisms underlying this disease have been elucidated over the past two decades, these molecular insights have failed to translate into efficacious therapy. The oncogenomic view of cancer suggests that terminal transformation reflects the sequential corruption of signal transduction circuits regulating key homeostatic mechanisms, whose multiplicity underlies the therapeutic resistance of most tumors to interventions targeting individual pathways. Conversely, the paucity of mechanistic insights into proximal pathophysiological processes that initiate and amplify oncogenic circuits preceding accumulation of mutations and transformation impedes development of effective prevention and therapy. In that context, guanylyl cyclase C (GCC), the intestinal receptor for the paracrine hormones guanylin and uroguanylin, whose early loss characterizes colorectal transformation, has emerged as a component of lineage-specific homeostatic programs organizing spatiotemporal patterning along the crypt––surface axis. Dysregulation of GCC signaling, reflecting hormone loss, promotes tumorigenesis through reprogramming of replicative and bioenergetic circuits and genomic instability. Compensatory upregulation of GCC in response to hormone loss provides a unique translational opportunity for prevention and treatment of colorectal tumors by hormone-replacement therapy.